Developments of Ḥadīth Riwāya in al-Andalus (2nd - 3rd Centuries of Hijriyya) - Muhammad Akmaluddin (Ulumuna, 2017)
This article examines the relations between Mālik schools and Andalusian scholars, the development of ḥadīth riwāyah and its relation with the social and cultural conditions in al-Andalus. Andalusian scholars, being influenced by views of Mālik b. Anas and his schools, made some tolerant standard for ḥadīth transmission. They did not make differences in narrative symbols and its hierarchy, except within the scope of the method. The validity of hadith is not solely determined by the strict criteria and subjective narrative, but also by the society and how they understand the narrative. There were social and cultural power relations with ḥadīth knowledge in al-Andalus that were influenced by critical and relative epistemology. Studies of hadith in al-Andalus focused more on the study of comprehension and meaning (sharh) of ḥadīth, which give practical benefit and applicable knowledge to the society.